Rapid Detection of VOCs from Pocket Park Surfaces for Health Risk Monitoring Using SnO2/Nb2C Sensors - Peng Wang; Yuhang Liu; Sheng Hu; Haoran Han; Liangchao Guo; Yan Xiao (Biosensors)
The organic volatile compound gases (VOCs) emitted by the rubber running tracks in the park pose a threat to human health. Currently, the challenge lies in how to detect the VOC gas concentration to ensure it is below the level that is harmful to human health. This study developed a low-power acetone gas sensor based on SnO2/Nb2C MXene composites, designed for monitoring acetone gas in pocket park rubber tracks at room temperature. Nb2C MXene was combined with SnO2 nanoparticles through a hydrothermal method, and the results showed that the SnO2/Nb2C MXene composite sensor (SnM-2) exhibited a response value of 146.5% in detecting 1 ppm acetone gas, with a response time of 155 s and a recovery time of 295 s. This performance was significantly better than that of the pure SnO2 sensor, with a 6-fold increase in response value. Additionally, the sensor exhibits excellent selectivity against VOCs, such as ethanol, formaldehyde, and isopropanol, with good stability (~20 days) and reversibility (~50). It can accurately recognize acetone gas concentrations and has been successfully used to simulate rubber track environments and provide accurate acetone concentration data. This study provides a feasible solution for monitoring VOCs in rubber tracks and the foundation for the development of low-power, high-performance, and 2D MXene gas sensors.